2012
DOI: 10.1039/c2dt31249b
|View full text |Cite
|
Sign up to set email alerts
|

Structure and luminescence behaviour of as-synthesized, calcined, and restored MgAlEu-LDH with high crystallinity

Abstract: Highly crystalline Eu(3+)-incorporated MgAl layered double hydroxides (LDHs) were synthesized by the homogeneous precipitation method. For the crystals as-prepared, after their calcination from 200-1000 °C, and, further, after restoration in a Na(2)CO(3) solution, the structural and luminescent changes were investigated for the first time. Eu(3+) ions with a coordination number of, probably, 8, were incorporated into the hydrotalcite layer, which led to a basal spacing (d(basal)) increase, microstrain formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 87 publications
0
19
0
1
Order By: Relevance
“…And the size distribution lies in the region of 600–2000, 700–2000, and 600–2000 nm in both deionized water and DMEM. The organic/LDH nanohybrids usually showed formation of agglomerate due to the strong interparticle interaction [59, 60]. However, it did not mean that the primary particles of nanohybrids with ~200 nm lateral size strongly aggregated in the aqueous media, as they can be easily stabilized into small assembly of particles under appropriate treatment of stabilizing agents.…”
Section: Resultsmentioning
confidence: 99%
“…And the size distribution lies in the region of 600–2000, 700–2000, and 600–2000 nm in both deionized water and DMEM. The organic/LDH nanohybrids usually showed formation of agglomerate due to the strong interparticle interaction [59, 60]. However, it did not mean that the primary particles of nanohybrids with ~200 nm lateral size strongly aggregated in the aqueous media, as they can be easily stabilized into small assembly of particles under appropriate treatment of stabilizing agents.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that some rare-earth ions, such as lanthanide Tb 3+ , Eu 3+ , and Nd 3+ , can be doped into the octahedral lattice of the brucite-like layer [27,28]. Incorporation of Tb 3+ has been achieved by coprecipitation method under ambient conditions [29].…”
Section: Rare-earth-doped Luminescencementioning
confidence: 98%
“…Synthetic LDHs exhibit a wide flexibility in their composition, as a score of metal cations and polyvalent anions can be introduced in the structure, tuning their chemico-physical properties [1][2][3]. By changing both the interlayer and the metal components, LDHs have been tuned towards different applications, serving as heterogeneous catalysts, catalyst supports [4], water treatment agents [5], luminescent materials [6][7][8][9], etc. Synthetic LDHs exhibit a wide flexibility in their composition, as a score of metal cations and polyvalent anions can be introduced in the structure, tuning their chemico-physical properties [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Controlled thermal decomposition of LDHs converts their structure into a mixed metal oxyhydroxide phase, before reaching a fully oxidic end product [5,9,19,20]. Starting from the oxyhydroxide phase, the lamellar LDH structure can be recovered by re-hydrating the product in aqueous solutions containing anions, a phenomenon known as the memory effect [5,9,[20][21][22][23]. During this process, selective adsorption of dissolved anionic species A n− can efficiently occur, as indicated by the large anion exchange capacity observed for thermally treated samples [24].…”
Section: Introductionmentioning
confidence: 99%